Rethinking Islam in Europe Contemporary Approaches in Islamic Religious Education and Theology - Sejdini, Zekirija (De Gruyter, 2022)
After Islamic theology was given a place at universities in German-speaking areas, certain issues in the Islamic theology and religious pedagogy took on greater importance and moved to the forefront of discussion. A collection of various articles by the author, this book focuses on developing an understanding of Islam that is context-sensitive and takes both the Islamic tradition and the new European context into account.